Integrative Versus Distributive Bargaining: Choosing a Problem Resolution Process - Coleman, Rick; Fraser, C. (Relations industrielles / Industrial Relations, 1979)
This paper examines the antithetical nature of two methods of resolving conflict through negotiation, and suggests there is an appropriate process depending upon how a party views the problem, and how he perceives it being viewed by his opponent.